Damage and seismic velocity structure of pulverized rocks near the San Andreas Fault. Issue 6 (28th June 2013) - Rempe, Marieke; Mitchell, Thomas; Renner, Jörg; Nippress, Stuart; Ben‐Zion, Yehuda; Rockwell, Thomas
Abstract: [1] A combination of seismic refraction tomography, laboratory ultrasonic velocity measurements, and microstructural observations was used to study the shallow velocity structure of a strand of the San Andreas fault (SAF) just south of Littlerock, California. The examined site has a strongly asymmetric damage structure with respect to the SAF core. The conglomerates to the southwest show little to no damage, whereas a ~100 m wide damage zone exists to the northeast with a ~50 m wide zone of pulverized granite adjacent to the fault core. Seismic P‐wave velocities of the damaged and pulverized granite were investigated over a range of scales. In situ seismic velocity imaging was performed on three overlapping profiles normal to the SAF with lengths of 350 m, 50 m, and 25 m. In the laboratory, ultrasonic velocities were measured on centimeter‐ to decimeter‐sized samples taken along the in situ profiles. The samples were also investigated microstructurally. Micro‐scale fracture damage intensifies with increasing proximity to the fault core, allowing a subdivision of the damage zone into several sections. Laboratory‐derived velocities in each section display varying degrees of anisotropy, and combined with microfracture analysis suggest an evolving damage fabric. Pulverized rocks close to the fault exhibit a preferred fault‐parallel orientation of microfractures, resulting in the lowest P‐wave velocity orientated in fault‐perpendicular direction. Closest to the fault, pulverized rocks exhibit a gouge‐like fabric that is transitional to the fault core. Comparison of absolute velocities shows a scaling effect from field to laboratory for the intact rocks. A similar scaling effect is absent for the pulverized rocks, suggesting that they are dominated by micro‐scale damage. Fault‐parallel damage fabrics are consistent with existing models for pulverized‐rock generation that predict strong dynamic reductions in fault‐normal stress. Our observations provide important constraints for theoretical models and imaging fault damage properties at depth using remote methods. Key Points: Seismic velocities of pulverized rocks agree with their microstructures. Pulverized rock velocities scale, suggesting that micro‐scale damage dominates. Damage fabric is consistent with existing models for pulverized rock generation.